2019
DOI: 10.1093/treephys/tpz133
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling reveals the crucial biological pathways involved in cold response in Moso bamboo (Phyllostachys edulis)

Abstract: Most bamboo species including Moso bamboo (Phyllostachys edulis) are tropical or subtropical plants that greatly contribute to human well-being. Low temperature is one of the main environmental factors restricting bamboo growth and geographic distribution. Our knowledge of the molecular changes during bamboo adaption to cold stress remains limited. Here, we provided a general overview of the cold-responsive transcriptional profiles in Moso bamboo by systematically analyzing its transcriptomic response under co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 86 publications
2
11
0
Order By: Relevance
“…We have identified 17 PAP members in Moso bamboo, which is similar to the previously reported number of PAPs in chickpeas, tomatoes, and Jatropha curcas [33,52,55]. In view of the huge differences in genome size between these plant species, the proteins encoded by the PAP genes of the same species have greater conservation [56].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We have identified 17 PAP members in Moso bamboo, which is similar to the previously reported number of PAPs in chickpeas, tomatoes, and Jatropha curcas [33,52,55]. In view of the huge differences in genome size between these plant species, the proteins encoded by the PAP genes of the same species have greater conservation [56].…”
Section: Discussionsupporting
confidence: 81%
“…The seeds of Moso bamboo were thoroughly washed with sterile water and soaked in sterile water for 16 h and then germinated in the soil at 22 • C under long-day conditions (16 h of cool white, fluorescent light, photon flux of 70 µmol m −2 •s −1 ) [33]. Then, we irrigated the soil with 1/3 × Hoagland's normal phosphorus (1.0 mmol/L KH 2 PO 4 ) nutrient solution every three days.…”
Section: Plant Materials Growth Conditions and Treatmentsmentioning
confidence: 99%
“…The bamboo in the Sichuan, Chongqing, Guizhou and Shaanxi Provinces is mainly grown in the Sichuan Basin where the elevation ranges from 300 to 700 m. Influenced by human activities, such as reclamation, bamboo forest grows less in regions with an elevation lower than 200 m. Highland bamboo forests were also found in the Yunnan province. The limited elevation range of the distribution of bamboo forests is due to temperature decreasing as elevation increases [76,77].…”
Section: Classification Accuracy Assessmentmentioning
confidence: 99%
“…Furthermore, 35 members of trihelix transcription factors (TTFs) were observed to show higher expression in bamboo leaves and panicles in response to drought and salt stress treatments (Cheng, Xiong, et al, 2019). Liu, Wu, et al (2020) recently identified that TF responses to cold stress are specific to moso bamboo. Since the TFs act as regulatory switches for gene expression, both temporal and spatial, they are critical in understanding the fast growth, flowering behavior, and stress response in bamboos.…”
Section: Development Of Genomic Resources For Identifying Genes Undermentioning
confidence: 99%
“…(2013) recommended TIP41 and NTB as reference genes for the reliable quantification of candidate gene expressions for moso bamboo. In a latest transcriptomic investigation, Liu, Wu, et al (2020) had elucidated differentially expressed genes (DEGs) on cold response in moso bamboo, identifying more late‐responsive genes than early‐responsive ones under cold exposure. As many as 222 TFs belonging to 24 families and several C‐repeat/dehydration‐responsive element‐binding factor (CBF) elements were found up‐regulated under cold stress implying the presence of a complex cold response network in moso bamboo.…”
Section: Development Of Genomic Resources For Identifying Genes Undermentioning
confidence: 99%